Aplikasi Bimbingan Tugas Akhir Menggunakan Notifikasi Berbasis Android - Irma Salamah; Lindawati Lindawati; Hermika Yuliana Sitompul (STMIK Budi Darma, 2019)
This research provides a final assignment service application (MyAbita) as a monitoring system to carry out the guidance process. This application is made by utilizing technological developments. This application can be accessed online using Android in the data communication process. In the process of using it, this application will notify users. In the design process, this application is designed using the Rapid Application Development (RAD) method, making it easier for the application design process. In developing the system, this application uses android studio software and the programming languages used are Java, PHP, and XML. And for storing the database using MySQL. This application has been integrated online so that it can be used by students in conducting the final assignment guidance process and the lecturer can also monitor the progress of the guidance process at any time.